2019
DOI: 10.1038/s41401-019-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Alzheimer’s disease and global glucose metabolism revealed by the metabolic profile alterations of pancreatic tissue and serum in APP/PS1 transgenic mice

Abstract: Increasing evidence suggests that there is a correlation between type 2 diabetes mellitus (T2D) and Alzheimer's disease (AD). Increased Aβ polypeptide production in AD patients would promote metabolic abnormalities, insulin signaling dysfunction and perturbations in glucose utilization, thus leading to the onset of T2D. However, the metabolic mechanisms underlying the interplay between AD and its diabetes-promoting effects are not fully elucidated. Particularly, systematic metabolomics analysis has not been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Blood metabolomics is an attractive tool for agnostic exploration of disease pathways because metabolites are small molecules that re ect the interaction of genetic and environmental factors, readily cross the BBB and their levels are modi able through dietary or pharmacological interventions [23]. Some studies support the hypothesis that AD is a systemic disease characterized by impaired glucose metabolism, mitochondrial dysfunction, and abnormal BCAAs metabolism [24,25]. Valine, a branched-chain amino acid, quickly offers amino groups for the synthesis of glutamate, thus maintaining brain nitrogen homeostasis and indirectly affecting excitatory neurotransmitters [26].…”
Section: Discussionmentioning
confidence: 99%
“…Blood metabolomics is an attractive tool for agnostic exploration of disease pathways because metabolites are small molecules that re ect the interaction of genetic and environmental factors, readily cross the BBB and their levels are modi able through dietary or pharmacological interventions [23]. Some studies support the hypothesis that AD is a systemic disease characterized by impaired glucose metabolism, mitochondrial dysfunction, and abnormal BCAAs metabolism [24,25]. Valine, a branched-chain amino acid, quickly offers amino groups for the synthesis of glutamate, thus maintaining brain nitrogen homeostasis and indirectly affecting excitatory neurotransmitters [26].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have suggested an association between AD and impaired glucose metabolism that may be pronounced in those with type 2 diabetes and insulin resistance 47,48 . Prior fluorodeoxyglucose‐positron emission tomography (FDG‐PET) scans have suggested decreased brain metabolism across the spectrum of AD 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…As a mouse model of AD, APPswe/PS1dE9 (APP/PS1) is known to have typical AD-like pathologies and impaired cognition and memory. Studies assessing glucose metabolism in APP/PS1 mice have described glucose tolerance in standard diet-fed young mice [ 9 ]. Other studies that found young APP/PS1 mice fed with high-fat diet (HFD) demonstrated a phenotype of significantly impaired glucose tolerance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%